The Role of Primary Care in End of Life Care - Aghnaa Gayatri (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2018)
Primary Care has been acknowledged to be the solution towards the achievement of “Health for All” as declared in the Declaration of Alma Ata1. Its importance has been further emphasized in the World Health Organization (WHO) 2008 Report2, where the changing world is in dire need of health care that surpasses all boundaries and can be delivered to all. It is stated that current health systems that are mostly hospital-based pose the risk of fragmented and uncoordinated care for the people. The move towards primary care is aimed at solving this problem amongst many others.One of the features that distinguishes primary care from other levels of care is that it addresses the needs of people irrespective of their age, gender, and disease, thus caring for individuals from the very beginning of life until death3. Caring for the dying patient has been traditionally considered as palliative or hospice care which is being provided to terminally ill patients in secondary settings4. With the shift of population by the increasing of elderly people, chronic conditions also become a major health problem which can eventually lead to death, and these often occur at homes and at the nursing care centers5. Care for the dying patient should not be just about preparing the patient for death. It is important to manage the dying patient in terms of management of symptoms and providing psychological support. Primary care situated as the first line of health care has an important role in ensuring that end of life care is well provided from the earliest stage possible, in coordination with other services when necessary.......